THE WIKILEAKS´S CASE AND ANONYMITY: EFFECTS ON THE INFORMATION FREEDOM - Oliveira, Marlus Heriberto Arns de; Cella, José Renato Gaziero (Revista Eletrônica do Curso de Direito da UFSM, 2015)
The Constitution of the Federative Republic of Brazil, enacted in 1988 during the democratization process of the country after the end of an authoritarian regime preceded by several others that show a non-democratic tradition in the Brazilian Republic, remained still remnants an authoritarian Patronizing and Paternalist state, the example of the final part of the Article 5, item IV, which claims to be the free expression of thought, but forbids anonymity, prohibition which deserves to be rethought, especially on the internet, where the navigation data of people deserve protection, as well as their rights to remain anonymous, a fact which entails the need for reflection on the scope and how best to interpret the constitutional provision cited, a debate that, in the proposed article will deal think the ideas of paternalism, authoritarianism and freedom, whose focus will be about within the Internet, social networks and the Knowledge Society.